470. Concomitant Antibiotic Use and Death Among a National Cohort of Veterans With Clostridium difficile Infection (CDI). (26th November 2018) - Appaneal, Haley; Caffrey, Aisling; LaPlante, Kerry
Abstract: Background: Antibiotic use is a well-known risk factor for development of CDI, and there is preliminary evidence suggesting concomitant antibiotic use may result in poor outcomes, including death. This work investigated the effect of concomitant antibiotic exposure during CDI treatment on mortality among patients with CDI. Methods: We conducted a national retrospective study of Veterans with a first CDI between 2010 and 2014, defined as a positive C. difficile toxin(s) and no episode in the year prior. Those treated with guideline recommended CDI treatment were included (10–14 days of PO or IV metronidazole, PO or PR vancomycin, or fidaxomicin). The exposure of interest was any non-CDI antibiotic use during CDI treatment; and the outcome was all cause death within 30 days of the end of CDI treatment. Inverse probability of treatment weighted Cox proportional hazards models were used to estimate the effect of concomitant antibiotic use on time to mortality. Weights were derived from propensity score modeling of the probability of exposure to antibiotics during CDI treatment as a function of potential confounders. Sensitivity analyses by antibiotic class were conducted. Results: Of the 9, 517 patients included in the study cohort, mean age was 65.3 years (±SD 14.6), 92.5% ( n = 8, 802) were male, and 75.03% ( n = 7, 141) were white. Half were exposed to non-CDI antibiotics during CDI treatment (51.8%, n = 4, 925) and 8.9% ( n = 849) died. In unadjusted and adjusted analyses, concomitant antibiotic use was associated with death (HR 5.74, 95% CI 4.75–6.93; aHR 2.39, 95% CI 2.07–2.75). Advanced generation cephalosporin (aHR 2.36, 95% CI 2.05–2.71), β-lactam/β-lactamase inhibitor combinations (aHR 1.45, 95% CI 1.16–1.82), and clindamycin (aHR 1.95, 95% CI 1.26–3.02) were associated with death, while fluoroquinolone use was not (aHR 0.97, 95% CI 0.84–1.12) Conclusion: Among our national cohort, concomitant antibiotic use was common during CDI treatment. Any concomitant antibiotic use increased the risk of death; however, results suggest risk might vary by antibiotic class. Results support continued efforts in the reduction of unnecessary antibiotic use during CDI treatment, and future studies into which antibiotics may have the least risk of death when treatment is necessary. Disclosures: H. Appaneal, Merck: Grant Investigator, Research support. A. Caffrey, Pfizer: Investigator, Research support. Merck: Investigator, Research support. The Medicines Company: Investigator, Research support. K. LaPlante, Merck: Grant Investigator, Research grant. Pfizer Pharmaceuticals: Grant Investigator, Research grant. Allergan: Scientific Advisor, Honorarium. Ocean Spray Cranberries, Inc.: Grant Investigator and Scientific Advisor, Honorarium. Achaogen, Inc.: Scientific Advisor, Honorarium. Zavante Therapeutics, Inc.: Scientific Advisor, Honorarium.